Bridging Tradition and Policy: Local Regulation and the Sustainability of the Hemaq Beniung Indigenous Forest - Dini Zulfiani; Thalita Rifda Khaerani; Wheny Khristianto (Green Insight Solutions, 2025)
Indigenous forests in Indonesia are vital ecological and cultural assets, yet they often face legal uncertainty and limited recognition within formal governance systems. To address this, the Regional Regulation of West Kutai Regency Number 6 of 2014 concerning the Protection of Customary Forests, Historical Sites, Flora and Fauna, and Environmental Conservation in West Kutai Regency provides formal recognition and a legal framework for safeguarding indigenous forest management. This study analyzes how the regulation bridges indigenous law with formal governance to ensure the sustainability of the Hemaq Beniung Indigenous Forest in Juaq Asa Village, East Kalimantan. A qualitative descriptive approach was employed, drawing on interviews with government officials, indigenous leaders, and forestry stakeholders, as well as document analysis and field observations. The findings show that regional regulation establishes a foundation for protection, supervision, and conservation, while strengthening indigenous rights and community participation. Its implementation has enhanced legal recognition, fostered collaboration between government and communities, and improved conservation outcomes for biodiversity. However, challenges remain, including limited enforcement resources and pressures from illegal logging and forest conversion. This study emphasizes the significance of local regulation as a vital policy instrument for incorporating customary practices into formal governance, thereby enhancing both ecological sustainability and the resilience of indigenous communities.